Mielopati et causa Tumor Medula Spinalis : Laporan kasus - Fitriyani, Fitriyani; Iskandar, Puji Fauziyyah (Medula, 2024)
Myelopathy is a description of a neurological deficit caused by spinal cord abnormalities. One of the conditions that can cause myelopathy is a spinal cord tumor. Spinal cord abnormalities based on type and location are assessed using the American Spinal Injury Association (ASIA) scale which is divided into grades A, B, C, and D. The prevalence of spinal cord tumors is 15% of all central nervous system tumors. Based on its location, spinal cord tumors are divided into intradural and extradural. Manifestations of spinal cord tumors consist of sensory, motor, and autonomic disturbances according to the location of the compression lesion. The diagnosis is made based on anamnesis, physical examination and supporting examinations. In patients with spinal cord tumors, radiological investigations can be carried out. The principle of management of spinal cord tumors is to remove the tumor to restore maximum neurological function. The choice of further management for spinal cord tumors is consulted with a neurosurgeon. The prognosis of spinal cord tumors depends on the severity of the patient. Case report Mrs. W, 41 years old with diagnosis myelopathy et causa tumor medula spinalis based on anamnesis and physical examination and supporting investigation given therapy NaCl 0,9% infusion 20 drops per minute, vit B12 3x1 tablet, sodium diclofenac 2 x 50 mg tablet, and consulted with neurosurgeon to obtain further management.